'I was blinded by work' - Abd Razak, Dzulkifli (2006)
THE education world rejoiced when TIME magazine (Dec 27, 2004) named Korean Dr Hwang Woosuk as one of the People Who Mattered in 2004. The choice seemed appropriate at the time. Veterinarian Dr Hwang Woosuk was the first to clone human embryos capable of yielding viable stem cells that might one day cure countless diseases. He became a celebrity, a hero and a treasure for Asia's technological powerhouse overnight. Last year would have been another landmark for science, a rare honour for Asia ahead of American and European counterparts. It was a year of opportunities, specifically for South Korea, to showcase its newfound biotechnological talents.